Vasosensory reflex responses are mediated through the afferents originating from vascular plexuses in anaesthetised rats - SANJEEV K. SINGH,; SHRIPAD B. DESHPANDE, (International Journal of Pharma and Bio Sciences, 2017)
In the neurotomised animals, venom-induced mean arterial pressure (MAP) and respiratory rate (RR) changes were markedly attenuated but not the heart rate (HR) changes indicating the existence of additional afferent pathway. Hence, further sets of experiments were performed to explore the afferents. Albino rats were anaesthetised with an intra-peritoneal injection of urethane (1.5 g/kg). Tracheostomy was performed to keep the airway patent. Femoral artery was cannulated proximally for the recording of blood pressure and distally to inject the chemicals/venom. The effect of venom on MAP, HR and RR were recorded at every 5 min for 60 min and presented as mean ± SEM. Intra-arterial injection of Mesobuthus tamulus venom elicits vasosensory reflexes producing immediate hyperventilatory, intermediate hypertensive and delayed bradycardiac responses in anaesthetised rats. After ipsilateral nerve sectioning, the RR and MAP changes were attenuated significantly but not the HR changes. Pre-treatment with neurotomy plus vagotomy plus local anaesthetics, blocked all the venom-induced cardiorespiratory responses viz changes in RR, MAP and HR. The observations of this study provide evidence for afferent pathways in somatic nerves and also through the perivascular nerve plexuses.